The Platonic agnosticism in the Plato’s Phaedo - Xavier, Dennys Garcia (Revista Archai, 2016)
The aim of the paper is to analyse the epistemological problem involving statements concerning the soul and the afterlife in the context of the Phaedo. Special attention is dedicated to the theoretical elements that cast doubts on aspects considered essential for his metaphysics, namely: the relationship between the body and the soul, death as good and/or evil, the eternal nature of the soul as well as the values and limitations of the evidence and counterproofs presented in the dramatic context of the text. Keywords: Plato, Agnosticism, Phaedo, Body, Soul.